Income tax evasion: Tax elasticity, welfare, and revenue - Max Gillman (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
This paper provides a general equilibrium model of income tax evasion. As functions of the share of income reported, the paper contributes an analytic derivation of the tax elasticity of taxable income, the welfare cost of the tax, and government revenue as a percent of output. It shows how an increase in the tax rate causes the tax elasticity and welfare cost to increase in magnitude by more than with zero evasion. Keeping constant the ratio of income tax revenue to output, as shown to be consistent with certain US evidence, a rising productivity of the goods sector induces less evasion and thereby allows tax rate reduction. The paper derives conditions for a stable share of income tax revenue in output with dependence upon the tax elasticity of reporting income. Examples are provided with less and more productive economies in terms of the tax elasticity of reported income, the welfare cost of taxation and the tax revenue as a percent of output, with sensitivity analysis with respect to leisure preference and goods productivity. Discussion focuses on how the tax evasion analysis may help explain such fiscal tax policy as the postwar US income tax rate reductions with discussion of tax acts and government fiscal multipliers. Fiscal policy with tax evasion included shows how tax rate reduction induces less tax evasion, a lower welfare cost of taxation, and makes for a stable income tax share of output.
Keywords: E13; H21; H26; H30; H68; K34; K42; O11; 330; Optimal Evasion; Tax Law; Welfare; Tax Elasticity; Revenue; Productivity; Development